2014
DOI: 10.1021/np4011037
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexadepsipeptides of the Isaridin Class from the Marine-Derived Fungus Beauveria felina EN-135

Abstract: Three new cyclohexadepsipeptides of the isaridin class including isaridin G (1), desmethylisaridin G (2), and desmethylisaridin C1 (3), along with three related known metabolites (4-6), were isolated and identified from the marine bryozoan-derived fungus Beauveria felina EN-135. The structures of these compounds were elucidated on the basis of extensive spectroscopic analysis, and the structures and absolute configurations of compounds 1-3 were confirmed by single-crystal X-ray diffraction analysis. The crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…Previous reports revealed that IDTs possessed various bioactivities including antibiotic [4,5] and anti-insectan potency [6,7] as well as tremorgenic mammalian mycotoxicity [8,9]. During our investigation on marine-derived fungi, a series of structurally interesting secondary metabolites such as cyclohexadepsipeptides [10], diketopiperazine alkaloids [11], and diphenylketones [12] were discovered. Recently, we focused our attention on Penicillium sp.…”
Section: Introductionmentioning
confidence: 97%
“…Previous reports revealed that IDTs possessed various bioactivities including antibiotic [4,5] and anti-insectan potency [6,7] as well as tremorgenic mammalian mycotoxicity [8,9]. During our investigation on marine-derived fungi, a series of structurally interesting secondary metabolites such as cyclohexadepsipeptides [10], diketopiperazine alkaloids [11], and diphenylketones [12] were discovered. Recently, we focused our attention on Penicillium sp.…”
Section: Introductionmentioning
confidence: 97%
“…Chloramphenicol and amphotericin B were used as positive controls against the bacteria and fungi, respectively. Evaluation of brine shrimp lethality against A. salina was performed as previously reported [17]. …”
Section: Methodsmentioning
confidence: 99%
“…and B. felina fungi. Du et al [169] reported the isolation of three new isaridins, namely, isaridin G, desmethylisaridin G, and desmethylisaridin C1. The structures of these compounds were elucidated by the X-ray crystallographic method.…”
Section: Classification Of Marine Resourcesmentioning
confidence: 99%